Heritage conservation as a bridge to sustainability assessing thermal performance and the preservation of identity through heritage conservation in the Mediterranean city of Nablus - M. Salameh, Muna (2022)
Heritage conservation can revive vernacular architectural methods of construction which naturally embody sustainable design concepts. This research investigates and highlights the intrinsic value of her itage conservation in building a sustainable society; from an environmental, economic, and social per spectives. This research is an evaluation of a unique case of heritage conservation in the city of Nablus, Palestine, at both architectural and urban scales. The investigation concluded that traditional passive design solutions have many advantages over modern ones. It was found that the thermal performance of a conserved traditional building was more effective, making it more sustainable than its modern coun terpart with the same function. Further, the investigation concluded that heritage conservation is core to protecting identity in its preservation of the past for future generations, especially in an occupied area, such as Nablus. This study aims to highlight the vast scope and application of heritage conservation with regards to innovative and sustainable solutions in a modern urban society. 2021 THE AUTHORS. Published by Elsevier BV on behalf of Faculty of Engineering, Ain Shams Uni versity. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/ by-nc-nd/4.0/).